Penggunaan Alih Kode dan Campur Kode oleh Penyiar Radio di RRI Pro 2 Padang - Fernando Julianto; Agustina Agustina (Persona: Kajian Bahasa dan Sastra, 2022)
This study describes the types of code-switching and code-mixing of RRI Pro 2 Padang and their causal factors. This type of research is qualitative research with a descriptive method. The population in this study were radio broadcasters at RRI Pro 2 Padang. To obtain the data needed in this study, the authors used data collection techniques using the listening method, which has done by listening to the language used to observe code-mixing and code-switching by radio broadcasters at RRI Pro 2 Padang. The steps taken in data collection are as follows: (1) downloading the results of broadcasts made by the broadcaster of RRI Pro 2 Padang on the official Youtube channel by RRI Pro 2 Padang, (2) listening to the results of the download of broadcast broadcasts and recording the language spoken, (3) clarifying the data that has been recorded in the code-switching and code-mixing group, (4) analyzing the factors causing code switching and code mixing by broadcasters at RRI Pro 2 Padang. The results of this study are as follows: (1) the most dominant type of code-switching used by broadcasters at RRI Pro 2 Padang is external code-switching compared to internal code-switching. (2) the factor causing the occurrence of code-switching events by radio broadcasters at RRI Pro 2 Padang is the speaker factor or the speaker himself. Then, the factors causing the occurrence of code-switching events that are the least found are due to the speech opponent or listener factor. (3) the type of code-mixing that often appears is outer code-mixing. On the other hand, code-mixing that rarely occurs is inner code-mixing. (4) the factor causing the occurrence of code-mixing t that most often appears is the role identification factor. Meanwhile, the factor that caused the code-mixing that slightly appeared by radio broadcasters at RRI Pro 2 Padang was the speaker factor.